2007
DOI: 10.1089/fpd.2007.0026
|View full text |Cite
|
Sign up to set email alerts
|

Retail Meat Consumption and the Acquisition of Antimicrobial ResistantEscherichia coliCausing Urinary Tract Infections: A Case–Control Study

Abstract: This study provides epidemiologic evidence that antimicrobial resistant, UTI-causing E. coli could have a food reservoir, possibly in poultry or pork.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(117 citation statements)
references
References 29 publications
(37 reference statements)
9
102
1
2
Order By: Relevance
“…Exposure to commercial-scale farm raised chickens 17 and consumption of retail meat 19 have been shown to increase individuals' risk for carriage of and infection by antibioticresistant E. coli , and the causal link between the carriage of resistant fecal flora in human populations and the use of antibiotics in farm animals has been amply demonstrated. 15,18,21 Conditions of poor sanitation are thought to play an important role in the widespread dissemination of resistant fecal bacteria in developing countries, 25,26 but the degree of risk in such settings caused by medical versus agricultural use of antibiotics is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to commercial-scale farm raised chickens 17 and consumption of retail meat 19 have been shown to increase individuals' risk for carriage of and infection by antibioticresistant E. coli , and the causal link between the carriage of resistant fecal flora in human populations and the use of antibiotics in farm animals has been amply demonstrated. 15,18,21 Conditions of poor sanitation are thought to play an important role in the widespread dissemination of resistant fecal bacteria in developing countries, 25,26 but the degree of risk in such settings caused by medical versus agricultural use of antibiotics is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…17 The spread of resistance factors from animal to human flora, including interbacterial species transmission, has been documented or is highly suspected in E. coli , Camphylobacter spp., 15 Enterococcus spp., 18 and other bacteria. Exposure to drug resistant animal flora can lead to disease 19,20 and prevalent carriage of resistant bacteria in human populations. 18,21 Low level antibiotics use also may contribute to resistance, by selecting low-level resistance strains.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, detection of a specifi c transmission route (e.g., foodborne) could not be directly addressed in this study. However, an earlier study, on the basis of epidemiologic data, has implicated frequent consumption of chicken and pork in the development of drug-resistant UTIs (31). Also, limited reproducibility of the ERIC2 PCR may have contributed to an underestimation of the number of clonal groups, particularly those clonal groups with only a few members (32).…”
Section: Discussionmentioning
confidence: 99%
“…Collaborative efforts have begun between the WHO-AGISAR and the FAO to implement integrated foodborne pathogen and AMR surveillance in the poultry, beef, pig and aquaculture value chains across Asia and Africa. The aim of these international collaborative efforts is to strengthen national capacities for AMR surveillance and to fill some of the data and information gaps to inform the development of appropriate national policies for several industries including good animal husbandry, health and hygiene [53].…”
Section: Animal Husbandry and Waste Managementmentioning
confidence: 99%
“…There are studies that cover a range of issues including but not limited to the uncertainties about the use of antibiotics in food animals and the risk posed to human health [62,63]; the epidemiological and molecular evidence for the spread of resistance from food animals to man [53,60,61,64]; and the benefits and risks of antimicrobial use in food-producing animals [65,66]. Despite the numerous studies focused on these issues, the WHO surveillance report (2014) indicated that there are major gaps associated with the surveillance and sharing of data around resistance in foodborne bacteria and its relationship with animal and human health [4].…”
Section: Food Safetymentioning
confidence: 99%